1982
DOI: 10.1002/bjs.1800690722
|View full text |Cite
|
Sign up to set email alerts
|

Reduced catheter sepsis and prolonged catheter life using a tunnelled silicone rubber catheter for total parenteral nutrition

Abstract: One hundred and five patients were given total parenteral nutrition (TPN) for an average of 15 days via centrally placed venous catheters. Thirty-seven polyvinyl chloride (PVC) and 80 silicone rubber catheters were used. All the silicone rubber and 8 of the PVC catheters were buried in a subcutaneous tunnel. When silicone rubber catheters were used, there was significantly less catheter sepsis (P much less than 0.01), catheter life was prolonged by 50 per cent and fewer catheter insertions per patient were nec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1983
1983
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…Strikingly, the incidence of local and systemic catheter-related infection was very low, although the catheters were not equipped with a Dacron cuff and subcutaneously tunneled. As outlined by different authors, this special design reduces the risk of infection by inhibiting bacterial ascension from the skin (14,151. This low rate of infection in this series is mainly due to the short duration of the catheters, which correlates with the effective collection of the PBSC.…”
Section: Discussionmentioning
confidence: 99%
“…Strikingly, the incidence of local and systemic catheter-related infection was very low, although the catheters were not equipped with a Dacron cuff and subcutaneously tunneled. As outlined by different authors, this special design reduces the risk of infection by inhibiting bacterial ascension from the skin (14,151. This low rate of infection in this series is mainly due to the short duration of the catheters, which correlates with the effective collection of the PBSC.…”
Section: Discussionmentioning
confidence: 99%
“…They have been successfully applied in short-and long-dwelling catheters, dialysis machines and blood oxygenators [118]. Polysiloxane-based catheters used for parenteral nutrition have been shown to cause significantly less sepsis compared to alternative materials [119]. Patient compliance improved in comparison to that found with PVC catheters, due to the extended working life of the polysiloxane materials.…”
Section: Polysiloxanesmentioning
confidence: 99%
“…Other factors that need to be considered when reviewing studies reporting rates of CVC-associated BSIs (18) include different patient populations, the intent of catheter use (22) and the duration of use (14,23). Before the study, we predicted that rates calculated in the present study would be higher than those reported by the NNIS (14) because the NNIS uses all CVCs in the denominator data, regardless of duration.…”
Section: Central Venous Catheter Infectionsmentioning
confidence: 97%